AUDIT KOMUNIKASI PROGRAM ONE VILLAGE ONE COMMUNITY PT RAPP ESTATE BASERAH KABUPATEN KUANTAN SINGINGI - Atika Windi Astuti; Yasir " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
One Village One Community (OVOC) is a work program of Corporate Social Responsibility (CSR) of PT RAPP Estate Baserah Kuantan Singingi Regency. OVOC is one of the flagship programs of PT RAPP Estate Baserah Kuantan Singingi Regency which is a sub program of Integrated Faming System (IFS), therefore, it is necessary to evaluate in order to know the success of communication from the superior program, to know the strength or weakness that exist, to prevent greater failures in the future. To find out whether the activities carried out are running as planned or not, communication audits are required. The purpose of this study is to know the implementation of OVOC program in terms of program planning, program implementation and program impact.This study is based on the audit model of the communication communication of a public relations planning model with an evaluation model developed by Jim Prichitt and Bill Sherman and refers to the communication components of communicators, messages, recipients and effects. This model consists of three stages in carrying out the evaluation, the first is the planning that produces the preparation, the implementation that produces the implementation, and the third is the final result produce impact. This research uses descriptive qualitative method with purposive technique. Data collection techniques by conducting interviews, observation and documentation.The results showed that the communication audit of One Village One Community PT RAPP Estate Baserah Kuantan Singingi in the preparation stage of the concept of activities has been well planned because the understanding between the executor of the activities with the previously planned documentation data has been appropriate; in the implementation stage, the implementation is quite smooth, it is seen from the previously designed implementation of many appropriate, although found some of the less effective communication content on the message component so that the process of delivering the message delivered repeatedly in the implementation; and at the impact stage it is found that the great objectives of the expected program have been achieved, as well as the component effects indicating the success of the beneficiary attitudes seen from the cognitive, affective and conative components.Key Words: Communication Audit, CSR, One Village One Community